(untitled) (Tanzania Medical Journal, 2019)
Background The cubital fossa can be seen superficially as a depression on the anterior side of elbow. It is a common site for removal of blood for analysis, for blood transfusion and intravenous therapy. The superficial veins of upper limbs follow three major veins which are cephalic, basilica and median cubital veins which are variable among individuals. Objectives The aim of the study was to observe and describe patterns of superficial veins in the cubital fossa of MUHAS students, and to assess if there were variations of patterns between left and right cubital fossas, also between male and female participants. Methodology The cross sectional study was designed. Convenient sampling was used to select 170 participants among Muhimbili University students ranging from 21-34 years of age who had visible superficial veins at the cubital fossa. A tourniquet was tied at mid arm level and superficial veins in the cubital fossa were photographed and described into various patterns. Results The commonest pattern was Type A which is N shaped, where median antebrachial vein divides to median cephalic and median basilica which joins cephalic and basilica veins respectively with the percentage of 37.6%. Incidences of type B, C, D, E and F were 17.1%, 26.5 %, 1.8%, 15.3% and 1.8% respectively on the left cubital fossa. There were variations between left and right cubital fossa patterns among same individual in some participants and no variations between male and female superficial venous patterns of cubital fossa. Conclusion Understanding various patterns of superficial veins in the cubital fossa is important in clinical practices since it helps easy locating of common superficial veins in procedures such as venipuncture, blood transfusion, intravenous therapy and arteriovenous fistula. Also there are few studies done in Africa and no studies done in Tanzania about superficial venous patterns in the cubital fossa. Key words: superficial veins, cubital fossa, patterns.